2018
DOI: 10.1055/s-0038-1676298
|View full text |Cite
|
Sign up to set email alerts
|

Tension Pneumocephalus after Cervical Spine Surgery: A Case Report with Review of the Literature

Abstract: This is the case of a 66-year-old male with cervical myelopathy secondary to severe cervical stenosis manifesting as worsening dexterity and numbness in his right hand. The patient underwent C3–C6 laminoplasty with bilateral foraminotomies. During the procedure an incidental durotomy occurred which was patched intraoperatively with Duragen and Tisseel. At 1 month follow-up, the patient reported that he was doing well and skin sutures were removed. Two days later, the patient presented to the emergency departme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“… 3 Our patient also recovered quicker compared with cases treated with burr holes and dural repair. 2 It should be highlighted that it is difficult to draw definitive conclusions due to the heterogeneity of patient groups as well as small sample size, but – at least in our patient – dural repair with supportive care had similar, if not better, outcomes than reported cases that have been treated with burr holes.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“… 3 Our patient also recovered quicker compared with cases treated with burr holes and dural repair. 2 It should be highlighted that it is difficult to draw definitive conclusions due to the heterogeneity of patient groups as well as small sample size, but – at least in our patient – dural repair with supportive care had similar, if not better, outcomes than reported cases that have been treated with burr holes.…”
Section: Discussionmentioning
confidence: 58%
“…Similar cases of delayed presentation and leaking wounds have also been reported by Gupta et al and Maupin et al , both presenting 1 month after their operations. 2 , 7 Maupin et al reported a clean wound that had sutures removed 2 days prior to re-presentation; 2 Gupta et al did not comment on the wound prior to re-presentation. 7 In our case, we suggest that a delayed presentation of TP is still possible despite a superficially healed wound.…”
Section: Discussionmentioning
confidence: 99%